Identifying Code-Mixing by Influencers in Captions on Social Media: Instagram - Dewa Ayu Andhina Maretha Putri; Ni Nyoman Padmadewi; Luh Putu Artini (Soshum: Jurnal Sosial dan Humaniora, 2024)
People’s ability to communicate with another person through a combination of verbal and non-verbal means is called language. This study recognizes the use of language in code-mixing in societies of social media. The objective of this study is to identify and analyze the types of code-mixing that are used by bilingual influencers. The researcher adopted a qualitative approach using an observation schedule and sheet. The result showed there is the domination of one type of code-mixing that is used in the Instagram captions of the participant. According to Suwito (1983), there are four kinds of forms of code-mixing.  The four types of code-mixing are word insertion, phrase insertion, hybrid, and repetition. Phrase insertion became the most frequent type of codemixing that occurred in Instagram captions of those three influencers reaching 33.3%.